Ukrainian fortresses a study of a strongholds system from the early iron age in Podolia - Ławniczak, Marcin (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2016)
There are two levels of detailed characteristic of the aforementioned sites. The first is the construction aspect, such as the area of the site (within the fortifications only) and the shape of the fortifications. The second level of detailed characteristics is description and presentation of the natural factors surrounding the sites, such as landforms and its location regarding to watercourses and watersheds.
Keywords: microspatial analysis; fortified settlements; Podolia; Early Iron Age; Scythian time